2023
DOI: 10.1097/lvt.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of open versus laparoscopy-assisted versus pure laparoscopic versus robotic living donor hepatectomy

Abstract: The value of minimally invasive approaches for living donor hepatectomy remains unclear. Our aim was to compare the donor outcomes after open versus laparoscopy-assisted versus pure laparoscopic versus robotic living donor hepatectomy (OLDH vs. LALDH vs. PLLDH vs. RLDH). A systematic literature review of the MEDLINE, Cochrane Library, Embase, and Scopus databases was performed according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement (up to December 8, 2021). Random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Through a systematic review and meta-analysis, Ziogas et al aimed to compare donor outcomes after open living donor hepatectomy (OLDH) vs laparoscopy-assisted living donor hepatectomy (LALDH) vs pure laparoscopic living donor hepatectomy (PLLDH) vs robotic living donor hepatectomy (RLDH). 56 A total of 31 studies from multiple countries were included, spanning the time period of August 1997 to November 2019. It included 2013 OLDH, 739 LALDH, 959 PLLDH, and 92 RLDH patients.…”
Section: Live Donor Managementmentioning
confidence: 99%
“…Through a systematic review and meta-analysis, Ziogas et al aimed to compare donor outcomes after open living donor hepatectomy (OLDH) vs laparoscopy-assisted living donor hepatectomy (LALDH) vs pure laparoscopic living donor hepatectomy (PLLDH) vs robotic living donor hepatectomy (RLDH). 56 A total of 31 studies from multiple countries were included, spanning the time period of August 1997 to November 2019. It included 2013 OLDH, 739 LALDH, 959 PLLDH, and 92 RLDH patients.…”
Section: Live Donor Managementmentioning
confidence: 99%
“…63,64 A recent systematic review of 31 studies concluded a marginal benefit in estimated blood loss and length of hospital stay in favor of pure laparoscopic donor hepatectomy and robotic donor hepatectomy, when compared with open procedure. 65 Technological advancements in robotic platform with its superb optical system, wide range of motion and tremor-free instrumentation, has made significant progress in donor hepatectomies, but the complexity of these procedures limits them to transplant centers with high volume and experience. [66][67][68][69] In a retrospective observational study, the SFSS rate was 6.6% in robotic (n = 102) and 4.6% in open (n = 152) RL donor hepatectomy, which was not statistically significant.…”
Section: Type Of Surgery (Open Versus Lap Versus Robotic)mentioning
confidence: 99%
“…In the absence of high-quality evidence, parenchyma-sparing hepatectomy should be chosen over anatomic resection when there is a reasonable chance all disease will be resected with negative margins, as well as in patients at higher risk of postoperative liver failure. On the other hand, the minimally invasive approach is increasingly being used for liver resection and, as in other surgeries, has been associated with reduced blood loss and shorter length of stay [10][11][12][13][14]. A recent systematic review and meta-analysis including three randomized controlled trials comparing the minimally invasive approach with open surgery for the resection of CRLM showed lower complication rates in patients who underwent the minimally invasive approach, with comparable disease-free and overall survival rates [15].…”
mentioning
confidence: 99%